2004
DOI: 10.1074/jbc.m310739200
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Regulation of N-WASP Subcellular Localization and Function

Abstract: N-WASP is a member of the WASP family of proteins that regulate actin cytoskeleton remodeling. FAK is a cytoplasmic tyrosine kinase implicated in integrin signaling during cell migration. Here we identify a direct interaction between N-WASP and FAK and show that N-WASP is phosphorylated by FAK at a conserved tyrosine residue, Tyr 256 . We found that phosphorylation of Tyr 256 affected N-WASP nuclear localization, suggesting that phosphorylation of N-WASP by FAK may regulate its activity in vivo by altering its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
143
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 53 publications
(59 reference statements)
2
143
0
2
Order By: Relevance
“…In this regard, Cdc42 and phosphatidylinositol (3,4,5)-triphosphate binding with N-WASP as well as the tyrosine phosphorylation of N-WASP has been shown to induce N-WASP activity (23,24). We previously showed that both Cdc42 and FAK maintain AJs and restore basal endothelial permeability following chal- lenge with edemagenic agents (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Cdc42 and phosphatidylinositol (3,4,5)-triphosphate binding with N-WASP as well as the tyrosine phosphorylation of N-WASP has been shown to induce N-WASP activity (23,24). We previously showed that both Cdc42 and FAK maintain AJs and restore basal endothelial permeability following chal- lenge with edemagenic agents (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin Induces N-WASP Phosphorylation in a FAK-dependent Manner That Restores Barrier Function-Phosphorylation of N-WASP by tyrosine kinases such as FAK has been shown to induce its activation (24). We therefore addressed whether thrombin induces the phosphorylation of N-WASP in a FAK-dependent manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). It is noted that the association between FAK and N-WASP was also observed in NIH 3T3 cells (12). Given the coexistence of FAK and N-WASP within the same macromolecular complex in the seminiferous epithelium, the possible influence of FAK on N-WASP-mediated activation of the Arp2/3 complex was next examined.…”
Section: Overexpression Of Fak Mutants On Tyr 407 Alters Phosphorylationmentioning
confidence: 99%
“…FAK has recently been shown to influence actin-related protein (Arp) 2/3 complex-mediated actin nucleation, modulating actin cytoskeleton, through at least two mechanisms. These include blockade of neuronal Wiskott-Aldrich syndrome protein (N-WASP), an Arp2/3 activator (11), from entering the nucleus following FAK-mediated phosphorylation (12), as well as the direct interaction of FAK 4.1/ezrin/radixin/moesin domain with Arp3, which enhances Arp2/3 activity (13). In short, FAK harnesses multiple levels of control over actin polymerization.…”
mentioning
confidence: 99%